2020
DOI: 10.1001/jamanetworkopen.2020.25481
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors of Acute Kidney Injury During Diabetic Ketoacidosis in Children and Association With Neurocognitive Outcomes

Abstract: IMPORTANCEAcute kidney injury (AKI) occurs commonly during diabetic ketoacidosis (DKA) in children, but the underlying mechanisms and associations are unclear. OBJECTIVE To investigate risk factors for AKI and its association with neurocognitive outcomes in pediatric DKA. DESIGN, SETTING, AND PARTICIPANTSThis cohort study was a secondary analysis of data from the Pediatric Emergency Care Applied Research Network Fluid Therapies Under Investigation in DKA Study, a prospective, multicenter, randomized clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 39 publications
8
77
2
Order By: Relevance
“…Studies have shown the association of higher initial serum urea nitrogen, higher heart rate, higher glucose-corrected sodium and glucose concentrations, and lower pH with AKI. 11 , 13 , 14 In the present study, the authors found older age, presence of infection, and worse biochemical profile at presentation (lower pH, higher blood glucose, higher lactate, higher corrected sodium, and hyperchloremia) to be associated with AKI. These are quite similar to other studies reiterating the fact that volume depletion at the time of presentation is an important contributor to AKI.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Studies have shown the association of higher initial serum urea nitrogen, higher heart rate, higher glucose-corrected sodium and glucose concentrations, and lower pH with AKI. 11 , 13 , 14 In the present study, the authors found older age, presence of infection, and worse biochemical profile at presentation (lower pH, higher blood glucose, higher lactate, higher corrected sodium, and hyperchloremia) to be associated with AKI. These are quite similar to other studies reiterating the fact that volume depletion at the time of presentation is an important contributor to AKI.…”
supporting
confidence: 50%
“… 11 , 12 The largest cohort study to date was a secondary analysis of data from the PECARN DKA FLUID study in which AKI occurred in 584/1,359 DKA episodes (43%). 13 …”
mentioning
confidence: 99%
“… 17 A recent study demonstrated that children with AKI had lower scores on short-term memory tests during DKA and lower scores on neurocognitive testing, 3–6 months after recovery from DKA, implying that mechanisms for the development of both these complications are probably similar. 6 Among the therapeutic variables such as fluid rate and rate of fall of glucose, our study failed to identify any significant risk factors on multivariate analysis, which predisposed to the development of organ dysfunction. It would be interesting to see the relationship of inflammatory markers and their role in the development of organ dysfunction in DKA.…”
Section: Discussionmentioning
confidence: 65%
“…In line with these data, we found that copeptin concentrations were elevated during DKA and that lower venous pH associated with higher copeptin concentrations. This is particularly important considering that pH is one of the main risk factors for the development of AKI during DKA 39 …”
Section: Discussionmentioning
confidence: 99%